1997
DOI: 10.1136/hrt.78.5.456
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in treatment delay by paramedic ECG diagnosis of myocardial infarction with direct CCU admission

Abstract: Objectives-To establish the feasibility of training paramedics to diagnose acute myocardial infarction by ECG before hospital admission and whether direct paramedic coronary care admission, arranged by very high frequency (VHF) radio communication with the coronary care unit (CCU), would reduce delay of thrombolysis treatment. Design-Prospective controlled study. Setting-District general hospital CCU and a local district ambulance paramedic service. Patients-124 patients with ECG evidence of myocardial infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 18 publications
(12 reference statements)
1
37
1
Order By: Relevance
“…660 Two nonrandomized trials reported no significant reductions in mortality with the use of prehospital ECGs (LOE 2). 117,657 In one of these studies in-hospital all-cause mortality was 15.6% in a group of STEMI patients brought by EMS to the ED without prehospital ECGs, and 8.4% for patients who had a prehospital ECG and were brought directly to the critical care unit for fibrinolysis. 117 The study was not powered to detect a mortality difference.…”
Section: Consensus On Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…660 Two nonrandomized trials reported no significant reductions in mortality with the use of prehospital ECGs (LOE 2). 117,657 In one of these studies in-hospital all-cause mortality was 15.6% in a group of STEMI patients brought by EMS to the ED without prehospital ECGs, and 8.4% for patients who had a prehospital ECG and were brought directly to the critical care unit for fibrinolysis. 117 The study was not powered to detect a mortality difference.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Eight studies demonstrated a reduction in the door-to-needle time interval ranging from 20 to 60 minutes when physicianor paramedic-interpreted prehospital 12-lead ECG was used to evaluate patients with suspected AMI who are then treated with a fibrinolytic (LOE 1 649 -652 ; LOE 2 116,117,653,654 ).…”
Section: Consensus On Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…28 The successful interpretation of the 12 lead electrocardiography by trained paramedics has now been documented in several studies. [22][23][24][25][26][27][28][29][30][31][32][33] For example, a 5 year study in Canada showed that paramedics can accurately identify patients who would have the greatest likelihood of benefiting from early, aggressive thrombolytic therapy. 33 Moreover, a study in the UK compared paramedics and cardiologists; 22 paramedics received two days intensive training in interpretation of a 12 lead ECG followed by consolidation in the field, after which time it was demonstrated that there was no significant difference between the two groups in recognition of ST segment elevation.…”
Section: Lead Electrocardiographymentioning
confidence: 99%
“…While some authors express concerns regarding delays to treatment time associated with 12 lead electrocardiography use by paramedics, four independent studies have shown that while there may be an increase in time at the scene of between 4 and 10 minutes, on average the overall time to treatment is decreased. [29][30][31][32] Generally, the use of pre-hospital 12 lead electrocardiography appears to provide a multitude of benefits including deceased mortality, increased likelihood of receiving thrombolysis, increased likelihood of angioplasty, increased likelihood of CABG, and most importantly, decreased time to treatment. 27 Pre-hospital reperfusion Given that early thrombolytic therapy is highly desirable and that appropriately trained paramedics can effectively interpret 12 lead electrocardiography readings, the question then becomes: can appropriately skilled paramedics administer thrombolytic therapy in the pre-hospital setting, to further improve the chain of survival for patients with AMI?…”
Section: Lead Electrocardiographymentioning
confidence: 99%